Comparison of Weighted Moving Average Method with Double Exponential Smoothing in Estimating Production of Oil Palm Fruit - Putri Anggraini; Muhammad Amin; Nasrun Marpaung (Forum Kerjasama Pendidikan Tinggi, 2022)
Oil palm is one of the largest agricultural products in Indonesia and has high economic value and can improve the welfare of oil palm farmers. The research was conducted at PT. Agro Putra Lestari regarding palm oil production, having its address at Jln.Imam Bonjol No.179 Kisaran with the name of the leader being Mr. Anda Puta Lubis, SE, M, Ma. PT. Agro Putra Lestari is a company that produces palm fruit products which is still running. PT. Agro Putra Lestari spread across the Asahan area, including Meranti, Simondol 1, Simondol 2, Simondol 3, Lahan Camat, Sitampu Saring, Marpaung, Miri-Miri, Solo Baru, and Lahan Kembar. The problem that often occurs is the amount of oil palm fruit production which is fluctuating so that the company does not know the estimated production of oil palm fruit in the following month. PT. Agro Putra Lestari has difficulty in knowing the results of oil palm fruit production in the following month because of improper planning to predict the production and have not applied the comparison of the weighted moving average and double exponential smoothing methods in predicting the amount of oil palm fruit production at PT. Agro Putra Lestari. The data used is from June 2021 to May 2022. The results of the forecasting of the two methods are compared to find out which forecasting results have the smallest error value, where the smallest error value can be used as a reference for future oil palm fruit production.